A duplex-specific nuclease assisted photoelectrochemical biosensor based on MoS2@ReS2/Ti3C2 hybrid for ultrasensitive detection of colorectal cancer-related piRNA-31, 143. (1st September 2022) - Li, Juan; Tong, Yao; Sun, Zhiwei; Chen, Yuqing; Wang, Yunshan; Zhou, Lianqun; Jiang, Yanyan; Li, Peilong; Wang, Chuanxin; Du, Lutao
Abstract: piR-31, 143 has been identified as a potential biomarker for the diagnosis of colorectal cancer (CRC). However, the current detection methods have complicated operations and high cost, which restrict its clinical application. In the present work, we reported a new photoelectrochemical (PEC) biosensor based on MoS2 @ReS2 /Ti3 C2 hybrid and duplex-specific nuclease (DSN) assisted signal amplification mechanism for ultrasensitive detection of piRNA-31, 143 from human serum. The formation of the type I heterostructure between MoS2 and ReS2 and the doping of Ti3 C2 contributed to high photocurrent response. The presence of piR-31, 143 triggered the chain displacement reaction and enzymatic cyclic amplification reaction on the electrode surface with the assistance of DSN, leading to the collapse of the composite probe system. Consequently, the photocurrent of the PEC biosensor was proportional to the concentration of piR-31, 143. The linear detection range and calculated detection limit of the PEC biosensor were 10 −1 –10 6 fM and 23 aM, respectively. The stability of the photocurrent under 15 consecutive on-off irradiations (with a relative standard deviation of 1.17%) and the specific response to piR-31, 143 demonstrated the reliability of the PEC biosensor. In addition, the practicability of the PEC biosensor was verified by batch detection of human serum. The area under the receiver operating characteristic curve used to distinguish CRC patients from healthy controls was 0.942 with 100% specificity, demonstrating the developed method is a promising approach for the diagnosis of CRC. Statement of significance: The clinical translation of piRNAs for cancer diagnosis is hindered by efficacy of detection techniques due to tedious sample processing and costly instrumentation. Herein, we fabricated a photoelectrochemical biosensor for the ultrasensitive detection of piR-31, 143 with 10 μL serum in vitro. MoS2 @ReS2 /Ti3 C2 greatly enhances the photocurrent response while duplex-specific nuclease improves the detection sensitivity and avoids false positives. By transforming the recognition sequence of the probe, the sensor can be applied to a variety of piRNAs detection for different diseases. In addition, the electrode can be recycled which is beneficial to reduce the cost of detection. With suitable automation and further optimization, our work may serve as core component in the development of an accurate and efficient diagnosis method. Graphical abstract: Image, graphical abstract